Rising markups, common ownership, and technological capacities - Alexandra J. Gibbon; Jan Philip Schain (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2020)
This paper analyses the impact of common ownership on markups and innovation and adds to the discussion of the recently observed patterns of a long term rise in market power. We shed light on the inconclusiveness of results regarding the effects of common ownership on markups in the existing literature by exploiting industry technology classifications by the European Commission. Using a rich panel of European manufacturing firms from 2005 to 2016, we structurally infer markups and construct a measure of common ownership. Combining propensity score matching with a difference-in-differences estimator, we find an increase of firm markups by 3.1% after the first exposure tocommon ownership. While this effect is strongly pronounced in low-tech industries, we find no effect on markups in high-tech industries. In contrast, we measure a positive effect of common ownership on innovation activity in high-tech industries and no effectin low-tech industries. Both findings are consistent with recent theoretical findings in Lopéz and Vives (2019).
Keywords: L10; L41; L60; G23; G32; O34; 330; Competition; Common Ownership; Market Power; Industry Structure; Antitrust; Innovation